Exploring the use of gamification in human-centered agile-based requirements engineering - Fatima, Arsh; Shaheen, Asma; Ahmed, Sohaib; Fazal, Bushra; Ahmad, Faizan; Liew, Tze Wei; Ahmed, Zeeshan (Frontiers in Computer Science, 2024)
Gamification has become prevalent in educational settings, particularly in human-centered software engineering. Using gamified learning environments for comprehending software engineering concepts can significantly enhance students' human factors, including motivation, engagement, and cognitive and critical thinking skills. Software requirements engineering constitutes one of the disciplines in the software development lifecycle. Based on the literature concerning agile-based software requirements engineering, coping with changing user requirements and constant alterations is often challenging. Consequently, both students and software developers must thoroughly grasp agile-based software requirements engineering. Over the last few years, educators and researchers have crafted gamified learning environments for agile-based software requirements engineering activities. Therefore, this paper aims to investigate the effectiveness of agile-based software requirements engineering activities through a gamified design approach. For this purpose, an application, ReGile, was developed and evaluated with 87 second and third-year software engineering students using the M-3 evaluation framework. Overall, the results were promising. Students expressed satisfaction with ReGile's technological usability. They performed well (72.14%) in answering questions related to software requirements engineering and agile methodology concepts. Furthermore, gender-wise results indicated that male students outperformed female students when using ReGile.